2011
DOI: 10.1149/1.3572321
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Electrical Effects of the Dep-Anneal-Dep-Anneal (DADA) Process for HfO2 in High K/Metal Gate Stacks

Abstract: In this work we present physical and electrical characterization of HfO2 films deposited using the Dep-Anneal-Dep-Anneal (DADA) deposition scheme. Electrical results from MOSCAP devices fabricated using a low temperature (Gate Last-like) integration flow are presented. In addition we report detailed physical analyses of the films and changes in the films versus as-deposited ALD HfO2 and films undergoing a single post-deposition anneal and show the correlation between observed physical changes in the film and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(54 citation statements)
references
References 14 publications
5
49
0
Order By: Relevance
“…In comparing the DADA and PDA films it is also observed that the DADA films exhibit a higher level of ordering based on the higher intensity of the diffraction peak at 2θ ~51° even though both films received the same total thermal budget. This data indicates that the DADA process is leading to structural differences possibly due to enhanced nucleation of the crystalline phases for the cyclical process as opposed to the conventional PDA method, in keeping with our previously proposed model (17). Figure 3 shows the cross-sectional TEM images of the films used for GIIXRD analysis in Figure2.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…In comparing the DADA and PDA films it is also observed that the DADA films exhibit a higher level of ordering based on the higher intensity of the diffraction peak at 2θ ~51° even though both films received the same total thermal budget. This data indicates that the DADA process is leading to structural differences possibly due to enhanced nucleation of the crystalline phases for the cyclical process as opposed to the conventional PDA method, in keeping with our previously proposed model (17). Figure 3 shows the cross-sectional TEM images of the films used for GIIXRD analysis in Figure2.…”
Section: Resultssupporting
confidence: 80%
“…In contrast to PDA, which is ECS Transactions, 41 (2) 89-108 (2011) performed on thicker films than each individually processed layer within the DADA process, the removal of C accompanied by the uptake of Si appears to be enhanced due to the interspersed annealing scheme. In our previous study we also observed, based on cross-sectional transmission electron microscopy imaging, structural modifications due to the DADA process as well as low RMS roughness (on the order of amorphous HfO 2 ), as measured by atomic force microscopy, when comparing PDA with DADA films (17). Based on these observations we presented a proposed model for bottom up crystallization due to the DADA process.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Similar, to what has been found previously, crystallinity is found for the HfO 2 films undergoing anneal. (12,13,16,17) In addition, we find that the thicknesses of the HfO 2 as well as the SiO 2 as measured by HRTEM do not vary significantly based on the deposition process In order to better understand the changes in HfO 2 and interface layer thickness we developed an in-line, non-destructive measurement method based on a combination of spectroscopic ellipsometry (SE) and X-ray reflectivity (XRR), that has been reported by others previously. (22) In our case, we use center point measurements of the entire dielectric stack, including HfO 2 and SiO 2 , by SE, and of the HfO 2 only by XRR.…”
Section: Methodsmentioning
confidence: 96%
“…(14,15) In the context of these reported interspersed deposition and annealing processes we have also recently investigated and reported on improvements in ALD HfO 2 films grown by use of an analogous deposition and thermal annealing scheme. (16,17) This process is realized through multiple iterations of depositions and thermal anneals (Fig.1a) as opposed to a single deposition followed by a post-deposition anneal (PDA). The cyclical deposition and anneal process we have developed has been termed DADA and will be referred to as such herein.…”
Section: Introductionmentioning
confidence: 99%